COVID-19 pandemic impact on childhood vaccination coverage in Quebec, Canada - Marilou Kiely; Thowiba Mansour; Nicholas Brousseau; Ellen Rafferty; Yuba Raj Paudel; Manish Sadarangani; Lawrence W. Svenson; Joan L. Robinson; Arnaud Gagneur; S. Michelle Driedger; Shannon E. MacDonald (Taylor & Francis Group, 2022)
Response measures to mitigate the coronavirus disease 2019 pandemic impacted access to routine vaccination services. We evaluate the impact of the pandemic on routine infant vaccination uptake by comparing vaccination coverage, vaccine delays and doses administered in 2019 and 2020, in Quebec, Canada. Using a population-based vaccination registry, we compared vaccination coverage at 3, 5, 13 and 19 months of age between 2019 and 2020 cohorts each month from January to November. For vaccine delays, we measured the cumulative proportion vaccinated in each targeted cohort monthly. We also compared the measles-containing vaccines administered before 24 months of age between the same period in 2019 and 2020. A decline in vaccination coverage and children vaccinated on time was observed in all cohorts during the first months of the pandemic. The greatest impact was observed for the 18-month vaccination visit with a difference in vaccination coverage between both cohorts of 30.9% in May. Measles-containing doses administered during the first months of the pandemic were lower in 2020 compared with 2019: −21.1% in March (95%CI-21.6;-20.4), and −39.2% in April (95%CI-40.0;-38.2). After May, the coverage increased for all cohorts to reach pre-pandemic levels after a few months for most target ages. Routine childhood vaccinations were affected during the first months of the pandemic, but catch-up occurred thereafter and vaccination coverage in affected cohorts were very close to levels of 2019 after a few months of follow-up. Real-time monitoring of childhood vaccination is essential but also for other vaccination programs, severely affected by the pandemic.